Funcionarios de la Oficina de Sistemas. (UNED, 2024)
Aparece sentadas de izquierda a derecha Carmen María Gutiérrez Iglesias, Mirna Fonseca Alvarez, Zayra Flores Marchena, Carmen Lorena Palma Vargas, Xinia Zeledón Morales, Nuria Rodríguez Sama, Guiselle Hidalgo Molina. De pie de izquierda a derecha Donaval Neil Thompson, Manuel Murillo Alfaro, Rodolfo Artavia Jacks